Can we model cultural ecosystem services, and are we measuring the right things?. Issue 1 (26th October 2021) - Jones, Laurence; Boeri, Marco; Christie, Mike; Durance, Isabelle; Evans, Karl L.; Fletcher, David; Harrison, Laura; Jorgensen, Anna; Masante, Dario; McGinlay, James; Paterson, David M.; Schmucki, Reto; et al.
Abstract: Cultural ecosystem services (CES), a key aspect of nature's contributions to people, remain a challenge to incorporate into decision making. One contributing factor is the difficulty of defining and describing these, due partly to: ongoing poor understanding of what drives people to interact with nature, a lack of appropriate data to quantify these interactions, and basic difficulties in measuring and modelling the complex array of social, psychological and behavioural attributes which help explain people's actions. In this study we present a framework which develops the concepts of cultural capital, social capital and human capital as specific forms of human‐centred capital, in the context of their contribution to understanding CES. Each form of capital encompasses separate attributes of beneficiaries. Testing the framework with data from a separate trans‐disciplinary study illustrated that the framework was readily applicable to specific situations. A measure of cultural capital, EcoCentrism, explained more variation than a suite of seven demographic variables. Applying the framework also showed that despite using a wide range of explanatory variables, a large proportion of observed variation remained unaccounted for. This suggests that more work is needed to understand and to develop metrics which can measure additional factors which underlie peoples' motivations to engage with nature. The framework is applicable to other types of ecosystem service, and may also be useful for exploring relational values. A free Plain Language Summary can be found within the Supporting Information of this article. Abstract : A free Plain Language Summary can be found within the Supporting Information of this article.